Plant Microbes Symbiosis: Applied Facets 2014
DOI: 10.1007/978-81-322-2068-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal Fungi and Their Applications

Abstract: Ectomycorrhizal (ECM) fungi form association with relatively small number of plants that dominate boreal, temperate, Mediterranean, and some subtropical forest ecosystems. These plant species have been able to acquire metabolic capabilities through symbioses with ECM fungi, thus improving their mineral nutrition and growth in several ecological niches. Mycorrhizal fungi can also play several other important ecological roles, including the protection of plants from abiotic and biotic stresses. Several "targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 98 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, this work provides comparison of the two ITS regions, ITS1 and ITS2, for fungal communities assessment. Changes in ECM fungal communities have been registered in many investigations ( Mello et al, 2015b ). Hui et al (2011) have observed, in a Finnish forest, that a long-term exposition to Pb contamination can result in a shift in the composition of the ECM community associated with P. sylvestris L., as well as an increase in the abundance of the OTUs corresponding to the Thelephora genus and a decrease in the frequency of OTUs assigned to Pseudotomentella , Suillus , and Tylospora .…”
Section: Identification Of Ectomycorrhizal Fungi: From the Past To Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this work provides comparison of the two ITS regions, ITS1 and ITS2, for fungal communities assessment. Changes in ECM fungal communities have been registered in many investigations ( Mello et al, 2015b ). Hui et al (2011) have observed, in a Finnish forest, that a long-term exposition to Pb contamination can result in a shift in the composition of the ECM community associated with P. sylvestris L., as well as an increase in the abundance of the OTUs corresponding to the Thelephora genus and a decrease in the frequency of OTUs assigned to Pseudotomentella , Suillus , and Tylospora .…”
Section: Identification Of Ectomycorrhizal Fungi: From the Past To Thmentioning
confidence: 99%
“…From the ecological point of view, the development of the ECM symbiosis and of the fruiting bodies of T. melanosporum is associated to the formation of a burnt area (known by the French word brulé), characterized by little vegetation around their host plants because of the phytotoxic effects generated by the truffle metabolites and volatile organic compounds ( Splivallo et al, 2011 ). Metagenomics data applied to French truffle-grounds have showed a reduced fungal biodiversity, a dominance of T. melanosporum and a reduced presence both of the ECM Basidiomycota and of bacteria belonging to Pseudomonas and Flavobacteriaceae inside the brulé, together with a reduction of richness of arbuscular mycorrhizal fungi ( Napoli et al, 2010 ; Mello et al, 2011 , 2013 , 2015b ; Mello and Zampieri, 2017 ). In order to relate microbial community composition to ecological processes happening in the brulé, Zampieri et al (2016) applied a metaproteomics analysis to the brulé previously characterized by metagenomics, and cross-referenced the resulting proteins with a database they constructed, incorporating the metagenomics data for the organisms previously identified in this soil, including the black truffle T. melanosporum.…”
Section: Tools From T Melanosporum Genome Sequencmentioning
confidence: 99%
“…Because of their essential roles in ecosystem processes, belowground fungi are important for forest management and ecosystem restoration [17][18][19]. However, our understanding of the belowground ecosystem of forests is still limited due to the complexity of belowground fungal species [18,20], diverse forms of plant-fungi interactions [21,22], and the variable spatial structure within belowground forest.…”
Section: Introductionmentioning
confidence: 99%